Formulation and characterization, of aceclofenac microspheres by ionic crosslinking technique - Dillip Kumar Mohapatra; M. D. Dhanaraju; S. Selvadurai (International Journal of Pharmacy and Analytical Research, 2016)
Objective Present investigation describes the preparation of Aceclofenac microspheres by ionic cross linking technique followed by characterization of microspheres to evaluate the effect of polymer concentration and different crosslinking agents on physical properties and drug release profile of microspheres. Methods Aceclofenac Microspheres were prepared with polymer, sodium alginate at various concentrations using ionic cross linking agents Calcium Chloride (CaCl2), Barium Chloride (BaCl2) and Aluminum Sulfide (Al (SO4) 3). The microspheres were developed and the effect of sodium alginate concentration, cross linking agents was evaluated with respect to entrapment efficiency, particle size, surface characteristics and in vitro release behaviors with the incorporation efficiency. The solid microspheres were characterized by sieve analyzer, scanning electron microscope, differential scanning calorimetry, and in vitro drug release. Results The infrared spectroscopic study confirmed the absence of any drug polymer interaction. Differential scanning calorimetric analysis revealed that the drug was molecularly dispersed in the alginate microspheres matrices showing rough surface, which was confirmed by scanning electron microscopy study. The mean particle size and entrapment efficiency and in vitro release profile could be altered significantly by changing various formulation parameters to give a sustained release of drug from the microspheres. Conclusion It can be concluded that the formulation prepared by ionic cross linking method, has potential to deliver Aceclofenac in a controlled manner in a regular fashion over an extended period of time in comparison to all other formulations and can be adopted for a successful oral delivery of Aceclofenac for safe management of hypertension.